(untitled) (Journal of Management and Social Sciences, 2017)
Abstract Gender is a critical and central social constructivity with definitive implications for access to and control of crucial resources in human societies. Gender is therefore very deterministic relative to veritable access to power, resources and positions and ultimately influences people’s life chances. Nigeria, like other African countries, is patriarchal. Nigerian societies give more chances and priviledges to one gender than the other and this tend to manifest across institutions of societies with implications for national and continental development. Since gender systems and structures of Africa appear to remain immutable in demonstration and consequences, it is important to continue to interrogate their contours, implications and manifestations. It is against these backdrops that this article adopted Bodija market’s case to examine how gender hinders or enhances access to land for male and female traders in the market. This article engaged the elements of intricacies of market entry and produce sales based on gender. Data were gathered through thirty-eight (38) in-depth interviews (IDIs) and data were content analysed and presented as blended narratives and ethnographic summaries. Important findings were made and presented in this article. Keywords Gender, land access, Bodija market, Ibadan, Nigeria, Africa